Microscopic brain invasion in meningiomas previously classified as WHO grade I is not associated with patient outcome - Biczok, Annamaria; Jungk, Christine; Egensperger, Rupert; Deimling, Andreas von; Suchorska, Bogdana; Tonn, Joerg C.; Herold-Mende, Christel; Schichor, Christian (Journal of neuro-oncology, 2019)
For meningiomas, the 2016 revision of the WHO classification introduced brain invasion per se as a sufficient condition to classify as grade II. We analyzed whether meningiomas previously graded as WHO grade I differ in prognosis depending on the presence of microscopic brain invasion.
Gesehen am 04.02.2020